(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يهدف هذا البحث إلى التعرف على الاتجاه العام لإيرادات ضريبة دخل المهن والحرف الصناعية والتجارية وغير التجارية في سورية وبناء نموذج رياضي يساعد على التنبؤ بهذه الإيرادات وذلك خلال الفترة الممتدة من عام 1999 وحتى عام 2010 حيث تبين أن هذه السلسلة غير مستقرة وبأخذ سلسلة الفروقات الأولى والثانية تم تحويلها إلى سلسلة مستقرة يمكن استخدامها في التنبؤ المستقبلي. حيث يتم التعرف على نمط تغير هذه الإيرادات من أجل بناء نموذج يساعد على التنبؤ بها. وقد تم تطبيق الأساليب الإحصائية المتعلقة بالسلاسل الزمنية (نماذج الانحدار للسلاسل الزمنية ونماذج أريما ARIMA)) ونموذج السير العشوائي مع ثابت) حيث تم استخدامها لتحديد الاتجاه العام و التنبؤ بإيرادات ضريبة دخل المهن والحرف الصناعية والتجارية وغير التجارية في سورية وتوصلت الدراسة إلى أن هناك اتجاهاً متزايداً في الإيرادات الضريبية خلال الفترة المشار إليها، كما تم التوصل إلى أن أفضل نموذج للتنبؤ المستقبلي بالإيرادات الضريبية هو نموذج الانحدار من الدرجة الثالثة ونموذج ARIMA(0,2,2) ونموذج السير العشوائي مع ثابت ( (8868.18وذلك بناءً على عدة مؤشرات لاختبار جودة النماذج المذكورة دون الأخذ بعين الاعتبار التغيرات الطارئة والموسمية. This research aims to identify the trend of direct tax revenues in Syria and build a mathematical model helps to predict these revenues during the period from 1999 to 2010. It was found that this series is not stable and taking the first and second differences has been converted into a stable series can be used in the future predict. Also this research aims to recognition the changes these revenues in order to build a model helps to predict. Statistical methods relating Time Series (regression models for time series, models ARIMA and model random walk drift) has been applied here, to determine the overall trend and predict the revenue income tax professions and trades industrial, commercial and non-commercial in Syria. The results show that : A growing trend in tax revenues during the period referred to, has also been reached that the best model for predicting future tax revenue is the regression model of third-degree model ARIMA (0,2,2) model and random walk drift (8868.18), based on several indicators to test the quality the models listed without taking into account changes and seasonal